The West African Semiarid Tropics - Matlon, Peter J. (International Food Policy Research Institute, 1987)
The West African semiarid tropics (WASAT) are defined as those areas where precipitation exceeds potential evapotranspiration from two to seven months annually. This corresponds to mean annual rainfall limits of approximately 250 to 1,300 millimeters. The area encompasses all of Senegal, the Gambia, Burkina Faso, and Cape Verde; major southern portions of Mauritania, Mali, and Niger; and the northern portions of Ivory Coast, Ghana, Togo, Benin, and Nigeria. Except for Senegal, all are classified by the World Bank (1981b) as among the poorest third of the world's developing countries, with mean per capita incomes of $320 or less. These countries are experiencing rapid population growth and remain primarily rural.